Endodontic practice management with cone-beam computed tomography - Priyank Sethi; Ritu Tiwari; Maneesha Das; Mahesh Pratap Singh; Manish Agarwal; Alfred Joseph Ravikumar (Wolters Kluwer Medknow Publications, 2017)
Traditionally, conventional periapical radiology formed the backbone of endodontics for diagnosis, treatment planning, and management. One of the major associated gripes being the technique created two-dimensional images of three-dimensional (3D) structures, suffered magnification, superimposition, and distortion, leading to compromised diagnostic information. The need to analyze the area of interest in all the possible planes led to the introduction of cone-beam computed tomography (CBCT), a novel modality specifically designed to produce precise, undistorted 3D reconstructed images of the maxillofacial skeleton. CBCT is increasingly being embraced by various fields in dentistry, remarkably in endodontic practice. A systematic literature-based and book-based review was conducted using the keywords "CBCT in endodontics" and "endodontic applications of CBCT." This article hereby discusses the prospects of CBCT in endodontics with an emphasis on its application in diagnosis and management along with treatment outcome assessment.